PENGEMBANGAN QUIET BOOK BERBASIS MULTIMODAL SEBAGAI MEDIA PEMBELAJARAN PERKALIAN DAN PEMBAGIAN UNTUK NUMERASI SISWA KELAS II SEKOLAH DASAR - Endang Sri Wahyuni; Ahmad Syawaluddin; Siti Raihan (STKIP Subang, 2026)
This study aims to describe the development process and determine the feasibility of a multimodal-based quiet book as a learning medium for multiplication and division in numeracy for second-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The analysis stage was conducted to identify learning needs, student characteristics, and multiplication and division materials. The design stage included the preparation of learning objectives, media design, and the integration of QR codes linked to instructional videos and interactive quizzes. The development stage involved product creation and validation by media and material experts, while the implementation stage was carried out through small-group and large-group trials involving second-grade students. The results showed that the developed multimodal-based quiet book integrates visual, kinesthetic, and digital elements, creating an interactive and engaging learning experience. The validation results indicated that media expert assessment reached 95% (very feasible), material expert assessment reached 80.5% (feasible), small-group student trials reached 99% (very feasible), large-group student trials reached 99% (very feasible), and teacher responses reached 96% (very feasible). Based on these findings, the multimodal-based quiet book is declared very feasible to be used as a learning medium for teaching multiplication and division in numeracy for second-grade elementary school students, although it still requires minor improvements in material aspects such as illustration adjustments and more precise terminology.